Motivation For Learning Economics: Teacher Creativity - Syata, Wahyu Muh; Hindaryatiningsih, Nanik; Sabillah, Bellona Mardhatillah; Lewa, Muhammad Juwantho (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The Independent Learning Curriculum in Indonesia emphasizes flexibility in learning that is tailored to students' needs and interests. Teachers are expected to have teaching strategies that can increase students' learning motivation, especially in economics subjects that are often considered boring by some students. This study aims to examine the role of teacher creativity in increasing students' learning motivation in economics learning. The method used in this study is a literature study or literature review. The results of the study show that teacher creativity greatly influences student motivation. Creative teachers can design interesting learning materials, use innovative media, and create a fun and interactive learning atmosphere. This has a positive impact on students' interest and enthusiasm in taking economics lessons, as well as improving their learning outcomes. Teacher creativity, which is reflected in critical thinking skills, flexibility, and the ability to evaluate and adapt teaching methods to students' needs, plays an important role in the success of learning. This study concludes that creative teachers can create a more effective learning process, help students achieve academic goals, and develop competencies that are important for their future.